A Scalable Training-Free Diffusion Model for Uncertainty Quantification - Muhammad Rafid, Ali Haisam; Yin, Junqi; Geng, Yuwei; Liang, Siming; Bao, Feng; Ju, Lili; Zhang, Guannan (SC24-W: Workshops of the International Conference for High Performance Computing, Networking, Storage and Analysis, 2024)
Generative artificial intelligence extends beyond its success in image/text synthesis, proving itself a powerful uncertainty quantification (UQ) technique through its capability to sample from complex high-dimensional probability distributions. However, existing methods often require a complicated training process, which greatly hinders their applications to real-world UQ problems, especially in dynamic UQ tasks where the target probability distribution evolves rapidly with time. To alleviate this challenge, we have developed a scalable, training-free score-based diffusion model for high-dimensional sampling. We incorporate a parallel-in-time method into our diffusion model to use a large number of GPUs to solve the backward stochastic differential equation and generate new samples of the target distribution. Moreover, we also distribute the computation of the large matrix subtraction used by the training-free score estimator onto multiple GPUs available across all nodes. Compared to existing methods, our approach completely avoids training the score function, making it capable of adapting to rapid changes in the target probability distribution. We showcase the remarkable strong and weak scaling capabilities of the proposed method on the Frontier supercomputer, as well as its uncertainty reduction capability in hurricane predictions when coupled with AI-based foundation models.